Defining Advance Care Planning for Adults: A Consensus Definition From a Multidisciplinary Delphi Panel - Sudore, Rebecca L.; Lum, Hillary D.; You, John J.; Hanson, Laura C.; Meier, Diane E.; Pantilat, Steven Z.; Matlock, Daniel D.; Rietjens, Judith A.C.; Korfage, Ida J.; Ritchie, Christine S.; Kutner, Jean S.; Teno, Joan M.; et al. (Journal of pain and symptom management, 2017)
Despite increasing interest in advance care planning (ACP) and previous ACP descriptions, a consensus definition does not yet exist to guide clinical, research, and policy initiatives. The aim of this study was to develop a consensus definition of ACP for adults. We convened a Delphi panel of multidisciplinary, international ACP experts consisting of 52 clinicians, researchers, and policy leaders from four countries and a patient/surrogate advisory committee. We conducted 10 rounds using a modified Delphi method and qualitatively analyzed panelists' input. Panelists identified several themes lacking consensus and iteratively discussed and developed a final consensus definition. Panelists identified several tensions concerning ACP concepts such as whether the definition should focus on conversations vs. written advance directives; patients' values vs. treatment preferences; current shared decision making vs. future medical decisions; and who should be included in the process. The panel achieved a final consensus one-sentence definition and accompanying goals statement: “Advance care planning is a process that supports adults at any age or stage of health in understanding and sharing their personal values, life goals, and preferences regarding future medical care. The goal of advance care planning is to help ensure that people receive medical care that is consistent with their values, goals and preferences during serious and chronic illness.” The panel also described strategies to best support adults in ACP. A multidisciplinary Delphi panel developed a consensus definition for ACP for adults that can be used to inform implementation and measurement of ACP clinical, research, and policy initiatives.